К изучению фауны совок Крыма. Сообщение VII. Подсемейство Melicleptriinae (Noctuidae, Lepidoptera) - Ключко, 3.Ф. (Вестник зоологии, 1975)
The subfamily Belicleptriinae which is not numerous in the Palearctic is represented in the Crimea by 13 species, 7 of which are observed in the Crimean fauna for the first time. Chloridea maritima Gras 1., Ch. nubigera H. S., Apaustis rupicola Schiff. are new species in the Ukrainian fauna. Species of the genus Chloridea Dunc. widely distributed in the Holarctic and Palearctic are the most numerous.